Macroinvertebrados bentônicos dos sistemas aquáticos da estação de piscicultura do CEPTA/IBAMA, Pirassununga, SP - Oliveira, Heliana Rosely Neves (2006)
With the objective to verify the distribution and the taxonomic structure of the benthic macroinvertebrates fauna of water systems (reservoir, fisheries and channels) of the CEPTA/IBAMA (Pirassununga, SP), a study with two types of methodologies was carried out. The samples of the sediment in the reservoir had been carried out with the Ekman-Birge grab, and in the fisheries and the channels with artificial substrate. The assemblages of benthic macroinvertebrates had been analyzed taxonomic and structurally. The larvae of Chironomidae (Diptera) were the main organisms in all the environments. The predominance of Procladius sp. and Djalmabatista pulcher was observed in the two reservoirs. The spatial analysis of the taxa distribution in the depths, pointed out with to major variety of taxa in the less depth regions (< 2m) in the Represa Velha, in contrast of the Represa Nova. At the same time, the average densities of the organisms had been opposing in the two reservoirs, presenting respectively major and lesser values in the intermediate depths (>2<3m). Temporaly, major abundance of macroinvertebrates at the dry season was observed, where major number of individuals occurred, represented mainly for the Procladius sp. and D. pulcher. In the faunistic analysis with artificial substrate, Goeldichironomus maculatus was dominant. There was taxonomic similarity between the assemblages in the artificial substrates in the reservoirs, fisheries and channels. The cluster analysis between the sampling methods, clustering the fauna of the baskets with the artificial substrate in the two reservoirs, and the fauna collected with the Ekman-Birge grab. This result points out with respect to the problematic use of artificial substrate use as a tool to characterize the fauna of a system.